2020
DOI: 10.1111/obr.12990
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the impact of lifestyle interventions on body weight in postpartum women: A systematic review and meta‐analysis

Abstract: Summary The established efficacy in postpartum lifestyle interventions has not been translated into better outcomes. This systematic review and meta‐analysis assess the penetration (the proportion of women invited within the target population), implementation (fidelity), participation (the proportion of those invited who enrolled), and effect (weight loss compared to controls) (PIPE) of randomized controlled trials of lifestyle interventions in postpartum women (within two years after birth). MEDLINE, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 78 publications
0
47
0
Order By: Relevance
“…We included studies reporting the barriers and facilitators, experiences and perceptions to engaging in a healthy lifestyle (diet, physical activity and weight management) in women within 2 years postpartum or their HPs. Previous studies have shown the need for interventions in women within this timeframe as they face unique barriers relating to the newborn, young baby or toddler 18,23 . Qualitative, quantitative and mixed‐methods studies were included.…”
Section: Methodsmentioning
confidence: 99%
“…We included studies reporting the barriers and facilitators, experiences and perceptions to engaging in a healthy lifestyle (diet, physical activity and weight management) in women within 2 years postpartum or their HPs. Previous studies have shown the need for interventions in women within this timeframe as they face unique barriers relating to the newborn, young baby or toddler 18,23 . Qualitative, quantitative and mixed‐methods studies were included.…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review and meta-analysis is the first, to our knowledge, to evaluate the quantitative effects of various childhood obesity prevention policies on children's BMI and BMI-Z score in an interventional design. There are many systematic reviews or meta-analysis studies that have been performed in specific settings such as schools only [ 12 , 13 , 60 ] or were performed for single-axis interventions such as physical activity only [ 10 , 61 ], diet only [ 13 ] or with limited duration of intervention [ 62 ] or follow-up [ 63 , 64 ] and different age ranges [ 9 , 10 , 60 , 64 ]. The current comprehensive meta-analysis evaluated the isolated effects of settings, intervention materials, duration and length of follow up, with a focus on the adiposity-related outcome of BMI or BMI-Z score .…”
Section: Discussionmentioning
confidence: 99%
“…77 A similar lack of data exists for the reach of health behavior change programs in postpartum women, with or without histories of GDM, which is reflective of the fact that very few interventions were conducted under real-world conditions using pragmatic trial designs. 78 Participation rates among women with a history of GDM varies greatly, but the highest rates are reported by studies that incorporate the intervention within existing activities such as a parents' group or existing health services for postpartum women. 62,78 Recruitment conducted in person, particularly during pregnancy or early postpartum periods, is also more successful at engaging women.…”
Section: Penetration and Participationmentioning
confidence: 99%
“…78 Participation rates among women with a history of GDM varies greatly, but the highest rates are reported by studies that incorporate the intervention within existing activities such as a parents' group or existing health services for postpartum women. 62,78 Recruitment conducted in person, particularly during pregnancy or early postpartum periods, is also more successful at engaging women. 62 Penetration and participation challenges are still greater among ethnic minority groups.…”
Section: Penetration and Participationmentioning
confidence: 99%
See 1 more Smart Citation